Effectiveness of hydrogen dilution for designing amorphous to crystalline Si thin film in inductively coupled plasma assisted magnetron sputtering - Kyung Sik Shin (2018)
© 2015 The Japan Society of Applied Physics. Careful analysis and investigations of the formation mechanism of the microstructure of the hydrogenated nanocrystalline silicon (nc-Si:H) film is presented. A systematic approach is made to understand the transition from amorphous (a-Si:H) to crystalline (nc-Si:H) by incorporating hydrogen dilution using inductively coupled plasma (ICP) assisted magnetron sputtering. Film analysis and plasma diagnostics results reveal that one can design desired microstructure simply by controlling H2dilution and energy control in the plasmas.